2009
DOI: 10.1099/jmm.0.007476-0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Legionella longbeachae infection in intratracheally inoculated mice

Abstract: This study established an experimental model of replicative Legionella longbeachae infection in A/J mice. The animals were infected by intratracheal inoculation of 103–109 c.f.u. L. longbeachae serogroup 1 (USA clinical isolates D4968, D4969 and D4973). The inocula of 109, 108, 107 and 106 c.f.u. of all tested L. longbeachae serogroup 1 isolates were lethal for A/J mice. Inoculation of 105 c.f.u. L. longbeachae caused death in 90 % of the animals within 5 days, whilst inoculation of 104 c.f.u. caused sporadic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…Notably, the closely related, soil-living pathogen Legionella longbeachae lacks genes for flagellum biosynthesis and may thus avoid recognition by mammalian pattern recognition receptors such as NLRC4 (25,51,55). This feature may account for why L. longbeachae is highly and often lethal in mouse models of infection (46,56).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the closely related, soil-living pathogen Legionella longbeachae lacks genes for flagellum biosynthesis and may thus avoid recognition by mammalian pattern recognition receptors such as NLRC4 (25,51,55). This feature may account for why L. longbeachae is highly and often lethal in mouse models of infection (46,56).…”
Section: Discussionmentioning
confidence: 99%
“…While only A/J mice are permissive for replication of L. pneumophila , A/J, C57BL/6, and BALB/c mice are all permissive for replication of L. longbeachae (Asare et al, 2007; Gobin et al, 2009). Resistance of C57BL/6 and BALB/c mice to L. pneumophila has been attributed to polymorphisms in Nod-like receptor apoptosis inhibitory protein 5 ( naip5 ) allele that recognizes the C-terminus of flagellin (Wright et al, 2003; Molofsky et al, 2006; Ren et al, 2006; Lightfield et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A study of the ability of L. longbeachae isolates to infect guinea pigs also demonstrated that there was a substantial variation in the virulences of different L. longbeachae strains in this infection model (110). Strains of L. longbeachae serogroup 1 are highly virulent in mice, with the intratracheal inoculation of 10 3 bacteria capable of causing disease (148). Unlike L. pneumophila, mouse infection with L. longbeachae is not restricted to A mice, and both BALB/c and C57BL/6 mice are also susceptible to infection with serogroup 1 strains (148).…”
Section: Responses In Micementioning
confidence: 99%
“…However, even in A mice, the infection is self-limiting. The exception to the general rule of murine resistance to Legionella infection is L. longbeachae, which is highly virulent for a variety of inbred mouse strains (148). Several other Legionella species also replicate in murine macrophages (181,355) and, if given a high-enough inoculum, may also replicate in whole animals.…”
Section: Immune Responses To Legionella Infectionmentioning
confidence: 99%
See 1 more Smart Citation